High SARS-CoV-2 seroprevalence in HIV patients originating from sub-Saharan Africa in the Ile-de-France area: Seroprevalence of SARS-CoV-2 in HIV patients. Issue 2 (August 2022) - ABDI, Basma; NDOADOUMGUE, Aude Laetitia; DJEBARA, Siham; ZAFILAZA, Karen; PALICH, Romain; MAROT, Stéphane; SCHNEIDER, Luminata; WIRDEN, Marc; SEANG, Sophie; DUDOIT, Yasmine; TEYSSOU, Elisa; TUBIANA, Roland; et al.
Highlights: Higher SARS-CoV-2 seroprevalence in HIV patients in comparison to the general population in France. High SARS-CoV-2 seroprevalence in African sub-Saharan HIV patients. Active smoking is associated with a lower rate of SARS-CoV-2 antibodies.